2021
DOI: 10.3390/nu13030865
|View full text |Cite
|
Sign up to set email alerts
|

Circulating GLP-1 Levels as a Potential Indicator of Metabolic Syndrome Risk in Adult Women

Abstract: Glucagon-like peptide-1 (GLP-1), an incretin hormone, plays an important role in regulating glucose homeostasis. In this study, the applicability of circulating GLP-1 levels as an early indicator of metabolic syndrome (MetS) risk was examined. Women without diagnosed diseases were grouped according to their number of MetS risk factors (MetS RFs) (no RFs as Super-healthy, n = 61; one or two RFs as MetS risk carriers, n = 60; 3 ≤ RFs as MetS, n = 19). The circulating GLP-1 levels and homeostasis model assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
1
9
0
2
Order By: Relevance
“…We anticipated an increased secretion of GLP-1 [6,18,19,38] but, surprisingly, neither INT-777 nor RO5527239 modulated plasmatic concentration of GLP-1 in treated foz/foz mice. HFD-fed foz/foz mice with fasting hyperglycemia and severe hyperinsulinemia have GLP-1 levels higher than controls, which is in line with the study of Seon et al reporting that GLP-1 levels correlated with fasting insulinemia in adult with metabolic syndrome [39]. It is possible that further TGR5 stimulation would not further increase GLP-1 synthesis and secretion.…”
Section: Discussionsupporting
confidence: 87%
“…We anticipated an increased secretion of GLP-1 [6,18,19,38] but, surprisingly, neither INT-777 nor RO5527239 modulated plasmatic concentration of GLP-1 in treated foz/foz mice. HFD-fed foz/foz mice with fasting hyperglycemia and severe hyperinsulinemia have GLP-1 levels higher than controls, which is in line with the study of Seon et al reporting that GLP-1 levels correlated with fasting insulinemia in adult with metabolic syndrome [39]. It is possible that further TGR5 stimulation would not further increase GLP-1 synthesis and secretion.…”
Section: Discussionsupporting
confidence: 87%
“…The CV outcomes trials, SUSTAIN 6 and PIONEER 6, which were part of these programs, demonstrated CV benefits with s.c. semaglutide and CV non-inferiority with oral semaglutide vs placebo, respectively [ 14 , 15 ]. Although there have been several studies with GLP-1RAs demonstrating a significant reduction in hsCRP [ 16 , 17 ], the impact of semaglutide on hsCRP has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, most studies on satiety hormones assess their post-prandial levels or release, which is attenuated in metabolic disorders compared to a healthy status. In the fasting state, however, people with normal glucose tolerance had significantly lower GLP-1 plasma concentrations than people with T2D [ 40 , 41 ]. In a case-control study, GLP-1 levels were positively correlated with metabolic syndrome traits [ 41 ], whereas fasting GLP-1 was reduced in obese subjects following weight-loss diets [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the fasting state, however, people with normal glucose tolerance had significantly lower GLP-1 plasma concentrations than people with T2D [ 40 , 41 ]. In a case-control study, GLP-1 levels were positively correlated with metabolic syndrome traits [ 41 ], whereas fasting GLP-1 was reduced in obese subjects following weight-loss diets [ 42 , 43 ]. However, weight was not a parameter of our study and participants were instructed not to change their lifestyle including dietary habits during the course of the study.…”
Section: Discussionmentioning
confidence: 99%